Changes in glomerular filtration rate in liver recipients after reduced exposure to calcineurin inhibitors with concomitant everolimus administration within the first year after immunosuppression conversion - V. E. Syutkin; A. A. Salienko; S. V. Zhuravel; M. S. Novruzbekov (Вестник трансплантологии и искусственных органов, 2022)
Objective: to compare changes in estimated glomerular filtration rate (eGFR) in liver recipients with initially normal and impaired eGFR within the first year after immunosuppression conversion.Materials and methods. Enrolled in the study were 215 recipients of deceased-donor livers from February 2009 to February 2020, who received everolimus with dose reduction or complete withdrawal of calcineurin inhibitors (immunosuppression conversion, ISxC) for varying periods of time. GFR was measured using the MDRD-4 formula immediately before ISxC, then 3, 6, and 12 months after orthotopic liver transplantation (LTx). One month was considered an acceptable temporary deviation from the corresponding point.Results. At the time of ISxC, 32 (15%) of 215 recipients had normal renal function. Chronic kidney disease (CKD) increased in 60% of the recipients with normal eGFR by the end of the first year following ISxC; the fall in eGFR was particularly pronounced in older recipients. In the group with a baseline eGFR of 60–89 mL/min/1.73 m2, eGFR normalized in 62% of cases within 12 months; 28% of cases had no changes in renal function. In the subgroup with a pronounced decrease in eGFR at the time of ISxC, increased eGFR was observed as early as 1 month after ISxC, and the maximum was recorded after 3–6 months. The mean eGFR relative to baseline by month 3 after eGFR were higher for ISxC that was done in the first 2 months after LTx (19.7 ± 15.7 ml/minute/1.73 m2) than for ISxC done in the long-term period after LTx (10.1 ± 8.7 ml/minute/1.73 m2, p < 0.05).Conclusion. Changes in eGFR in liver recipients receiving EVR plus low-dose calcineurin inhibitor (CNI) depend on baseline eGFR and are multidirectional. The use of ISxC in the early post-LTx period led to a more pronounced improvement in eGFR. Maximal changes in eGFR were observed by 3–6 months after ISxC.